TECHNICAL SKILLS OVERWHELMING SOCIAL SKILLS OF OCCUPATIONAL HEALTH NURSING ON TEACHING METHODS - Syaifoel Hardy; Isak Jurun Hans Tukayo; Rijal Maulana; Ridha Afzal (Poltekkes Kemenkes Semarang, 2021)
The teaching of occupational health nursing (OHN) requires an emphasis on which one should be dominant between technical and social domain, as practiced in the industrial health care services. The purpose of this research is determine which skill domain is more dominant between technical and social skills in the OHN teaching-learning system. This type of study is quantitative approach with cross-sectional study design. The populations were nursing students, nursing practitioners, and nursing lecturers. The sampling technique is non-probability sampling taken online with a sample size of 130 respondents of Indonesian nurses in Indonesia. The data collection tool used a mixed questionnaire in a Likert Scale based on the Health Belief Model theory. The data were analyzed using the Paired Sample T-Test to see whether the results of this study were dominated by the technical or social skills domain. The validity and reliability test was carried out with a sample of 30 people. They were measured by looking at the r table and the Cronbach alpha value for each questionnaire statement, using the SPSS application with the Pearson Product Moment test. The T-Test result of SPSS shows 95 respondents (73.1%), perceived technical skills dominate the OHN work in industry, and 35 respondents (26.9%) in social skills, with a p-value of 0.000. In other words, the dominance of technical skills has a very close association to the teaching-learning system. The need for technical skills is much more dominant than social skills. OHN teaching needs to have an emphasis on technical skills, not the social domain.